Learners' perceptions of grammar learning through oral communicative activities : a study among the english preparatory 1 students in UNIMAS - Grace, Wong Sau Fah (Universiti Malaysia Sarawak, UNIMAS, 2009)
Learners’ perceptions play an important role in language learning. The sets of attitude, belief and psychology traits constituted learners’ point of views often determine the quality of students’ learning. This study aimed to address learners’ perceptions of grammar learning through OCA. The quantitative survey instrumented a questionnaire was done among 203 respondents who were students of English Preparatory 1 learners of UNIMAS. In particular, the study investigated into learners’ perceptions on the helpfulness of the approach, aspects in OCA that helped in grammar learning and activities that preferred by learners. The findings revealed that learners perceived the approach as helpful to a certain extent. It was found activities of authentic interactions were more welcomed than others. Besides, learners valued activities whereby teacher’s actively involved during language class. However, learners were not very confident in the area of language use. Learner perception is a useful aspect educational stakeholders may look into to ensure higher success rate in language learning.